2011
DOI: 10.1590/s0102-67202011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias para aumentar a ressecabilidade em pacientes com metástases hepáticas de tumores colorretais

Abstract: -Introduction: Nowadays, liver resections can be performed with acceptable morbi-mortality rates. In specialized centers, mortality as low as 1% can be achieved, even with the advent of new hepatotoxic chemotherapy regimens. In order to reduce morbidity and mortality, newer strategies can be undertaken, such as portal vein embolization, radiofrequency ablation techniques, re-hepatectomies, major vascular resections and two stages hepatectomies. Method -Literature review was conducted on sites search PubMed, BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Through these factors, strategies have been developed to increase resectability in patients with primary tumors and hepatic metastases 16 . Chemotherapy has become better developed, with new drugs, particularly for treating metastases, thus promoting better responses and enabling indications for surgical treatment among patients who earlier would not have been candidates for resection 4 , 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these factors, strategies have been developed to increase resectability in patients with primary tumors and hepatic metastases 16 . Chemotherapy has become better developed, with new drugs, particularly for treating metastases, thus promoting better responses and enabling indications for surgical treatment among patients who earlier would not have been candidates for resection 4 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Through these factors, strategies have been developed to increase resectability in patients with primary tumors and hepatic metastases 16 . Chemotherapy has become better developed, with new drugs, particularly for treating metastases, thus promoting better responses and enabling indications for surgical treatment among patients who earlier would not have been candidates for resection 4 , 16 . A recent study showed that in some situations the results from hepatectomy to treat colorectal and non-colorectal metastases were similar 6 , thus further expanding the group of patients who are candidates for hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…portal vein ligation for staged hepatectomy). [24][25][26] Observamos ainda mudança nos conceitos cirúrgicos, com o entendimento de que margens subcentimétricas podem garantir sobrevida tardia e a utilização crescente de técnicas poupadoras de parênquima. [27][28][29] Diversos estudos comparativos demonstraram que a realização de ressecções não-regradas mas com margens microscopicamente livres, visando a conservação de parênquima, não tem impacto negativo no prognóstico destes pacientes, cursando, ao contrário, com maior sobrevida após a recidiva hepática, por aumentar a chance de retratamento locorregional.…”
unclassified